2006
DOI: 10.1098/rstb.2006.1871
|View full text |Cite
|
Sign up to set email alerts
|

The role of enzyme dynamics and tunnelling in catalysing hydride transfer: studies of distal mutants of dihydrofolate reductase

Abstract: Residues M42 and G121 of Escherichia coli dihydrofolate reductase (ecDHFR) are on opposite sides of the catalytic centre (15 and 19 Å away from it, respectively). Theoretical studies have suggested that these distal residues might be part of a dynamics network coupled to the reaction catalysed at the active site. The ecDHFR mutant G121V has been extensively studied and appeared to have a significant effect on rate, but only a mild effect on the nature of H-transfer. The present work examines the effect of M42W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 67 publications
3
71
0
Order By: Relevance
“…Benkovic and coworkers showed that mutations of residues (M42 and G121) that are far from the active site affect the hydride transfer rates [18,46]. Based on equilibrium covariance matrix fluctuations of the C α atoms obtained from all atom MD simulations, Rod et al showed that interactions of M42 with other residues (H45, D28, S49) would also be involved in the CS→OS conformational transition [13].…”
Section: Resultsmentioning
confidence: 99%
“…Benkovic and coworkers showed that mutations of residues (M42 and G121) that are far from the active site affect the hydride transfer rates [18,46]. Based on equilibrium covariance matrix fluctuations of the C α atoms obtained from all atom MD simulations, Rod et al showed that interactions of M42 with other residues (H45, D28, S49) would also be involved in the CS→OS conformational transition [13].…”
Section: Resultsmentioning
confidence: 99%
“…Competitive KIE experiments were conducted with G121V-M42W by using a method as described (37,40). The findings were compared with those for the WT enzyme (35) and the two single mutants, G121V (40) and M42W (41). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three distal mutants were also studied (G121 V, M42W and G121V-M42W). [49][50][51] The mutants were found to exhibit different tunnelling patterns from the wild type (WT) and from each other: while the WT enzyme required no modification of the donor-acceptor distance to facilitate tunnelling, the single mutants did require some rearrangement to arrive at the appropriate tunnelling distance. The double mutant, on the other hand, required significant rearrangement before tunnelling could occur, thus showing a stronger temperature dependence than either of the single mutants.…”
Section: Dihydrofolate Reductasementioning
confidence: 99%